SUSTAINABILITAS DALAM PERKEMBANGAN PERMUKIMAN NELAYAN DI KELURAHAN TAMBAK WEDI, SURABAYA - Radian Zaki Rabbani; Rizvanda Ryan Savero; Kapindro Hari Sasmita (RUSTIC, 2022)
The development of coastal settlements in Indonesia are commonly less advanced rather than urban settlements. One of the cases is fisher settlements in Tambak Wedi village, Surabaya, where many problems occur such as poverty; the low quality of human resources; unmaintained sanitation; unoptimized utilization of natural resources; and so on. This research is aimed to assess the sustainability in development of the fisher village, and furthermore to propose some solutions. This research utilized descriptive, evaluative and development method involving the 3 aspects of Sustainability and the 17 points of SDGs (Sustainable Development Goals) as indicators of assessment. Economic and environment aspects were emphasized more in the evaluation since the urgency of the issues. It was found out that fishing economy in the village is lack of supporting facilities to sustain the livelihood pattern. The coastal environment is full of trashes from local houses and urban wastes which are furthermore causing diseases and pandemic. The economy of local people which depends mainly on fishing activity should be supported by availability of local markets to simplify selling their products. The coastal environment surrounding the village should be neutralized from wastes by availability of trash bins spread out across the settlements area as well as the availability of the main disposal places. It also needs to educate the local people to maintain their own environment to promote their healthy condition. Meanwhile, social life in the village needs some recreative public space to sustain their social interaction.